2017
DOI: 10.1209/0295-5075/117/47002
|View full text |Cite
|
Sign up to set email alerts
|

TiPdSn: A half Heusler compound with high thermoelectric performance

Abstract: The electronic, structural and thermoelectric properties of TiPdSn half Heusler material have been studied using density functional theory and semi classical Boltzmann transport theory. It has been found that TiPdSn is an indirect band gap semiconductor with band gap 0.48 eV. TiPdSn exhibits large power factor for p-type composition which is equal to 14.88 × 10 11 W/msK 2 at 700 K. The lattice thermal conductivity and relaxation time decrease with an increase in temperature. To analyze the stability of this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 36 publications
1
13
3
Order By: Relevance
“…Bulk modulus, B 0 , elastic contants, c 11 , c 12 , c 44 , Young’s modulus, Y , in GPa and Poisson ratio, ν. Literature date ara reported when available. b Ref , (EXP). c Ref , (EXP). d Ref , (EXP). e Ref , (THEO). f Ref , (THEO). g Ref , (THEO). …”
Section: Resultsmentioning
confidence: 99%
“…Bulk modulus, B 0 , elastic contants, c 11 , c 12 , c 44 , Young’s modulus, Y , in GPa and Poisson ratio, ν. Literature date ara reported when available. b Ref , (EXP). c Ref , (EXP). d Ref , (EXP). e Ref , (THEO). f Ref , (THEO). g Ref , (THEO). …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that heavy bands provide high Seebeck coefficients. 42,[53][54][55] The calculated data for the Seebeck coefficient is shown in Table 6. From the above data, we can see that BS (2H) has the smallest Seebeck coefficient among all the materials.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…It is also possible to replace some of the suitable elements (either X or Y or Z) from the half and full Heusler compounds by the electropositive elements (eg, Li) of suitable size, which results to forming a new kind of materials called Quaternary Heusler compounds. In the last few years, the Heusler compounds have been studied for their excellent thermoelectric uniqueness as well as the remarkable applications in superconductivity, spintronics, antiferrromagnetism, magnetoresistance, ferromagnetism, half metallicity, and the topological devices 12‐18 . In 2012, Fu et al have reported that the p‐type FeNbSb based half Heusler compound has the figure of merit ZT >1 (1.1) at 1100 K temperature, 19 which is a unique achievement in the thermoelectric materials at high temperature.…”
Section: Introductionmentioning
confidence: 99%